Formation universitaire en période de guerre en Ukraine : défis, enjeux, stratégies dans l’enseignement du FLE - Luchkevych, Viktoriia; Kost, Hanna (Neofilolog, 2025)
This study examines the challenges encountered by Ukrainian higher education, with a specific focus on the Ivan Franko National University of Lviv, since the onset of the Russian invasion. The research investigates how the university has responded to this crisis by adopting a “didactics of catastrophe” framework and introducing novel pedagogical methods tailored to the unique needs of students living through wartime. Emphasis is placed on the implementation of innovative teaching strategies such as flipped classrooms and design thinking, delivered in a hybrid format, to ensure uninterrupted French language learning and foster student well-being. The findings highlight the efficacy of these approaches in such a volatile environment, underlining the crucial role of flexibility and pedagogical adaptability during times of crisis.